Gambogic acid-loaded PEG–PCL nanoparticles act as an effective antitumor agent against gastric cancer. (2nd January 2018) - Zhang, Dinghu; Zou, Zhengyun; Ren, Wei; Qian, Hanqing; Cheng, Qianfeng; Ji, Liulian; Liu, Baorui; Liu, Qin
Abstract: Poor water solubility and side effects hampered the clinical application of gambogic acid (GA) in cancer therapy. Accordingly, GA-loaded polyethylene glycol-poly(ɛ-caprolactone) (PEG–PCL) nanoparticles (GA-NPs) were developed and administered peritumorally to evaluate their antitumor activity. The particle size, polydispersity index, encapsulation efficiency and loading capacity of GA-NPs were 143.78 ± 0.054 nm, 0.179 ± 0.004, 81.3 ± 2.5% and 14.8 ± 0.6%, respectively. In addition, GA-NPs showed excellent stability, good biocompatibility and sustained release profile. Endocytosis studies in vitro demonstrated that the GA-NPs were effectively taken up by tumor cells in a time-dependent manner. In vivo real-time imaging showed that the nanoparticles effectively accumulated within the tumor tissue after peritumoral administration. The cytotoxicity study revealed that the GA-NPs effectively inhibited the proliferation of gastric cancer cells . In vivo antitumor therapy with peritumoral injection of GA-NPs exhibited superior antitumor activity compared with free GA. Moreover, no toxicity was detected in any treatment group. Histological studies confirmed a lower cell density and a higher number of apoptotic cells in the GA-NPs group compared with the free GA group. Furthermore, the expression level of the cysteine proteases 3 precursor (pro-caspase3), a crucial component of cellular apoptotic pathways, was efficiently reduced in mice treated with GA-NPs. In conclusion, the GA-NPs system provided an efficient drug delivery platform for chemotherapy.